Diagnostics and age-related evolution of Lennox–Gastaut syndrome. Management in diverse patient age periods - E. D. Belousova; S. G. Burd; N. A. Ermolenko; K. Yu. Mukhin (Эпилепсия и пароксизмальные состояния)
Lennox–Gastaut syndrome is an epileptic encephalopathy with onset in childhood. The classical triad of diagnostic criteria is well known: 1) presence of various types of refractory epileptic seizures (tonic, atypical absences, myoclonic, tonic/atonic drop attacks, generalized tonic-clonic, focal); 2) cognitive disorders with frequent behavioral disorders (not always evident by the beginning of epileptic seizures); 3) generalized, slow (≤2.5 Hz) spike-wave activity of wakefulness and generalized paroxysmal fast activity on sleep electroencephalogram. Despite the seizure onset usually occurring before the age of 8 (peak at 3–5) years old, the Lennox–Gastaut syndrome is often featured with a lifelong course. Many patients with this syndrome suffer from refractory epilepsy in adulthood, however, not always being provided a proper syndromological diagnosis. Expanding the criteria to diagnose the Lennox–Gastaut syndrome discussed here would allow to choose a proper treatment algorithm. Rufinamide is the drug of the second choice in the adjunctive therapy of epileptic seizures associated with Lennox–Gastaut syndrome. However, a pediatric-to-adult clinic transition of patients with Lennox–Gastaut syndrome may pose some obstacles. Herein, an effective patient management requires not only seizure control, but also improvement of patient's quality of life by influencing cognitive and behavioral issues, sleep disorders, disability (both physical and social), educational problems and employment.